The UK Heritage Crafts Association - Daniel Carpenter (EXARC Journal, 2019)
The Heritage Crafts Association is the UK advocacy body for traditional heritage crafts. Working in partnership with Government and key agencies, it provides a focus for craftspeople, groups, societies and guilds, as well as individuals who care about the loss of traditional crafts skills, and works towards a healthy and sustainable framework for the future.